O discurso das narrativas populares em língua portuguesa - Lopes, Fernanda (2008)
This paper has as objective to search the way how the discourse is built in Brazilian folk tales, in the moment that these tales are used by subjects in their social interactions. During this research, we take popular tales as a mean of revealing identity values, as long as they re carry on, linguistically, the tradition and alive culture. The popular narratives used as sample was heard and copied by Luis da Câmara Cascudo and reunited in the book Contos Tradicionais do Brasil . These narratives appear, firstly, at Portuguese oral modality; because of this, they were submitted to the retextualização process, and put together in the mentioned book. To support our research, we seek in Discourse Analysis theory that allows putting together the social historical context, the production conditions and the ideology that compose the narratives we picked out. This way, the discourse builds and constitutes meanings from historical and cultural context. During this process, we could check folk tales revealing important cultural aspects that demonstrat a possible vision of the society. Following this perspective, it was very important the moment that we can consider them as genre of discourse and to look at how they can be organized. Above of all, we could see polyphonic mechanisms that constitutes this discourse. The objectives intended in this paper were reached, at the same time that our research put on notability the popular culture and showed up how the selecioned tales carry on themselves a truth effect using as tool our language